The Economic and Environmental Implications of the US Repudiation of the Kyoto Protocol and the Subsequent Deals in Bonn and Marrakech - ZhongXiang Zhang; Andreas Löschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
Taking account of sinks credits as agreed in Bonn and Marrakech, this paper illustrates how market power could be exerted in the absence of the US ratification under Annex 1 trading and explores the potential implications of non-competitive supply behavior for the international market of tradable permits, compliance costs for the remaining Annex 1 countries to meet their revised Kyoto targets, and the environmental effectiveness. Our results show that the US withdrawal from the Kyoto Protocol has great impact on the economic costs and environmental effectiveness of the Protocol since it would lead to no real emission reduction in all remaining Annex 1 regions. Depending on how market power is exerted by the dominant permit suppliers, the former Soviet Union and the Eastern European countries, the overall compliance costs of all remaining Annex 1 regions differ significantly. Moreover, curtailing permit supply by market power increases substantially the overall environmental effectiveness by cutting the amount of hot air being emitted into the atmosphere by more than half, although to much less extent than in the case of the US compliance.
Keywords: Q25; Q43; D43; Q48; 330; climate policy; emission trading; market power; Kyoto Protocol; Klimaschutz; Umweltabkommen; Umweltzertifikat; Marktmacht; Luftverunreinigung; Spieltheorie; Theorie; Klimaschutz; Vereinigte Staaten